Kinetic modelling of nutrient removal of petroleum industry wastewater remediation - Noor, A. (Institute of Electrical and Electronics Engineers Inc., 2021)
The wastewater generated from the petroleum industry is incredibly recalcitrant and requires a lot of energy to clean. As a result, managing the treatment of petroleum industry wastewater (PIWW) in underdeveloped nations is problematic. Co-treatment with domestic wastewater (DWW) is a viable solution to the problem. The study was conducted for co-treatment of PIWW with DWW, in a lab scale extended aeration (EAS) reactor. The outcome identifies that the maximum ammonia removal was achieved at 20 PIWW, which was 88.3. Among the studied kinetic model of nutrient removal, modified Stover-Kincannon model and Monod model was found fit with experimental data with the coefficient of correlation (R2) greater than 0.99 and 0.98 respectively, evidently postulate that these models can be used to predict the reactor's effectiveness for nutrient removal. Thus, EAS treatment plant can be build for the treatment of PIWW together with DWW. Â© 2021 IEEE.